Unlocking the potential of informal greenspaces: insights into ecosystem services, community benefits and urban integration - Arduino, Chloe, author; Solomon, Jennifer, advisor; Goldstein, Liba, committee member; LoTemplio, Sara, committee member (Colorado State University. Libraries, 2025)
Rapid urbanization requires cities to prioritize sustainable development and resident well-being. Urban greenspaces enhance city resilience and health, yet development and access barriers remain. Informal greenspaces (IGS) are liminal urban spaces such as vacant lots and brownfields that are minimally managed and randomly dispersed, providing a resource-efficient alternative to address the challenges of traditional greenspaces. While the benefits of IGS are increasingly recognized, understanding local use and community perspectives—particularly those of disadvantaged groups—is critical to aligning these spaces with diverse needs and for exploring the potential of integration into city planning. Our research aims to understand how residents interact with IGS, the perceived ecosystem services and benefits, and how these vary by socio-economic status. Additionally, perspectives from City officials provide insights into management priorities, challenges, and opportunities for integrating IGS into urban planning. Our study employed a mixed-methods approach, combining systematic observations and semi-structured interviews. Using GIS mapping, 15 sites were identified and categorized by socio-economic status. Interviews and observations at IGS sites offered valuable insights into user interactions and perceived ecosystem services. Additionally, interviews with City officials explored how IGS could be integrated into urban planning and managed in the future. Through grounded theory analysis, we identified themes reflecting frequently mentioned ideas to explore our research aims. Residents perceived multiple ecosystem services provided by IGS, including those benefiting ecological health, social cohesion, as well as unique personal well-being services. Cultural ecosystem services were most frequently noted, underscoring the cultural significance of these spaces. Potential differences in perceived ecosystem services among socio-economic groups suggest a need for further research to address diverse community needs. While many of our sites were used at least once, some were notably underutilized, seeing no visitors. City officials recognized multiple functions of IGS, both for human and ecological purposes and highlighted future management opportunities and challenges. This study emphasizes the potential importance of IGS in urban landscapes and initiates discussions on their future role.
Keywords: ecosystem services; socio-economic context; urban planning; informal greenspace; community perceptions; sustainable development